2007
DOI: 10.1038/nrn2277
|View full text |Cite
|
Sign up to set email alerts
|

Where do you know what you know? The representation of semantic knowledge in the human brain

Abstract: Mr M, a patient with semantic dementia--a neurodegenerative disease that is characterized by the gradual deterioration of semantic memory--was being driven through the countryside to visit a friend and was able to remind his wife where to turn along the not-recently-travelled route. Then, pointing at the sheep in the field, he asked her "What are those things?" Prior to the onset of symptoms in his late 40s, this man had normal semantic memory. What has gone wrong in his brain to produce this dramatic and sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

205
2,000
18
35

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 2,361 publications
(2,258 citation statements)
references
References 97 publications
205
2,000
18
35
Order By: Relevance
“…the "who", "what", "where" and "when"), irrespective of the part of speech that conveys them. According to the authors, this fits nicely with fMRI data showing ATL involvement in semantic combinatorial mechanisms (Pallier et al 2011), and connects to a larger literature on semantic memory and conceptual combination that assumes the ATL to be an amodal semantic hub (Baron et al 2010;Patterson et al 2007).…”
supporting
confidence: 80%
See 1 more Smart Citation
“…the "who", "what", "where" and "when"), irrespective of the part of speech that conveys them. According to the authors, this fits nicely with fMRI data showing ATL involvement in semantic combinatorial mechanisms (Pallier et al 2011), and connects to a larger literature on semantic memory and conceptual combination that assumes the ATL to be an amodal semantic hub (Baron et al 2010;Patterson et al 2007).…”
supporting
confidence: 80%
“…Another interpretation attributes a critical role to the aMTG in the integration of different types of information to derive the propositional meaning of a sentence (Bornkessel-Schlesewsky and Schlesewsky, 2013), a claim that connects with a larger literature on the role of this region in semantic memory and conceptual combination (cf. Baron et al 2010;Molinaro et al 2015;Patterson et al, 2007).…”
Section: Assignment Of Interpretively Relevant Roles: the Role Of Thementioning
confidence: 99%
“…Both of these regions are considered to be key regions of the semantic network. The anterior temporal lobe region has been described as a critical site for the convergence and processing of semantic information at an abstract and amodal level (Patterson et al, 2007;Lambon Ralph et al, 2009), and damage to this region has been suggested to result in a central loss of conceptual knowledge, affecting the identification and recognition of objects, persons and other classes of concepts across all sensory modalities. Alternately, Gainotti (Gainotti, 2014(Gainotti, , 2015 also highlights the importance of the ATL region in his influential model of semantic memory, but unlike the unitary semantic hub hypothesis, suggests that lexical-semantic representations rely to a greater extent on the left ATL while non-verbal representations depend mainly on the right ATL.…”
Section: Discussionmentioning
confidence: 99%
“…Semantic level processing, however, is thought to occur in more anterior regions of the temporal lobe. The anterior temporal pole is thought to serve as a semantic hub binding distributed features to form core semantic representations (reviewed in Patterson, Nestor, & Rogers, 2007; see also Jefferies, 2013;Visser, Jefferies, & Lambon Ralph, 2010), where regions located more anteriorly in the MTG serve as an interface between lexical input processing regions and the anterior temporal pole (e.g., Binney, Embleton, Jefferies, Parker, & Lambon Ralph, 2010), making the anterior temporal lobe (including the anterior MTG) one likely candidate for the neural locus of the relatedness effect in comprehension. Thus, the first aim of this study was to test whether damage to separate temporal lobe regions creates exaggerated relatedness effects in production vs. comprehension (i.e., posterior vs. anterior temporal lobe, respectively), as this would provide support for the assumptions that the competition creating semantic interference arises at different levels of the language system.…”
Section: Neural Substrates Of Semantic Interference 10mentioning
confidence: 99%
“…Structurally, the ILF connects the inferior posterior temporal lobe (a region thought to serve as an "entry point" affording access to lexical and semantic representations, e.g., Damasio, Tranel, Grabowski, Adolphs, & Damasio, 2004;Démonet, Thierry, & Cardebat, 2005; see also Bedny, McGill, & Thompson-Schill, 2008), with the ATL (a region though to support semantic processing; Patterson et al, 2007;Mummery et al, 2000). Combined functional gray matter and structural white matter neuroimaging experiments of healthy subjects reveal that this pathway mediates mapping lexical with semantic representations during comprehension (Saur et al, 2008(Saur et al, , 2010Wong, Chandrasekaran, Garibaldi, & Wong, 2011).…”
Section: Neural Substrates Of Semantic Interference 34mentioning
confidence: 99%